Evaluation of Data Exposure Risks on Unencrypted Application Layer Protocols in RT/RW Net "X" Community Network Using NIST SP 800-86 Framework - Reza Febriana; Muhammad Sidik Asyaky (Journal of Computer Networks, Architecture and High Performance Computing, 2026)
Security vulnerabilities in community-based networks, such as RT/RW Net, remain a critical concern due to the widespread use of unencrypted protocols. This study presents a quantitative evaluation of data exposure risks in application-layer protocols, focusing on HTTP traffic in local community networks. Using a network forensics approach based on the NIST SP 800-86 framework, traffic was captured and analyzed to measure the frequency and magnitude of sensitive data leaks using automated tools for network traffic analysis. The study quantified exposure across four key indicators: user credentials, session tokens, cookies, and personal information. The results indicated a high level of exposure, with analyzed HTTP packets successfully revealing sensitive data in plaintext, including usernames and passwords. Furthermore, statistical analysis of communication patterns identified significant opportunities for eavesdropping and session hijacking due to the lack of encryption standards. This evaluation provides empirical evidence of critical security gaps in RT/RW Net infrastructure and emphasizes the urgent need to transition to encrypted protocols (HTTPS). The findings provide a quantifiable risk assessment that can serve as a basis for implementing mitigation strategies in community-scale network management.